2019
DOI: 10.1007/s00261-019-02120-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of needle tract seeding after coaxial ultrasound-guided percutaneous biopsy for primary and metastatic tumors of the liver: report of a single institution

Abstract: Purpose The objective of this study was to determine the incidence of needle track seeding after ultrasound-guided percutaneous biopsy of indeterminate liver lesions with a coaxial biopsy system without any other additional intervention or ablation therapy. Methods We identified 172 patients in a retrospective cohort study who underwent ultrasound-guided biopsy due to a liver mass in our institution between 2007 and 2016. The same coaxial biopsy system was used in all patients, no consecutive ablation was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…Their results were: The contamination of the biopsy tracts was significantly higher in the cases of IB (32% vs. 0.8%) [ 36 ] and these were associated with a higher number of local recurrences [ 37 ]. The lower risk of local recurrence after CNB was confirmed in other studies [ 38 , 39 ]. At many musculoskeletal oncology centers, CNB is therefore favored over IB [ 6 , 12 , 36 ].…”
Section: Discussionsupporting
confidence: 70%
“…Their results were: The contamination of the biopsy tracts was significantly higher in the cases of IB (32% vs. 0.8%) [ 36 ] and these were associated with a higher number of local recurrences [ 37 ]. The lower risk of local recurrence after CNB was confirmed in other studies [ 38 , 39 ]. At many musculoskeletal oncology centers, CNB is therefore favored over IB [ 6 , 12 , 36 ].…”
Section: Discussionsupporting
confidence: 70%
“…Although studies have suggested that patients who underwent percutaneous biopsy for sarcoma are not at higher risk of developing local recurrence or needle tract metastasis, the use of heterogeneous biopsy techniques without differentiating between open or percutaneous biopsy with or without coaxial needles, data pooling of different sarcoma entities (mixing up bone sarcoma and STS or histological grading), and an overall limited number of cases of needle tract metastasis does not allow for definitive conclusions . In recent years, the use of coaxial sheathed biopsy needles has reduced the risk of malignant cell deposits in the needle tract . Even in the case of retained malignant cells, their clinical significance remains unclear in the era of modern perioperative chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Die Besonderheit koaxialer Nadelsysteme besteht darin, dass eine Führungshülse einmal vorgeführt wird und eine Nadel mehrfach über diese Hülse in die Zielläsion zur Probenentnahme vorgeschoben werden kann. Einige Anwender setzen dieses System auch für die sonografisch gestützte Punktion ein [29]. Ein wichtiger Aspekt CT-gestützter Punktionen ist die optimale Lagerung, bevor das Planungs-CT in Spiraltechnik akquiriert wird.…”
Section: Computertomografisch Gestützte Punktionunclassified